2021
DOI: 10.3390/ijerph18063249
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Satisfaction to Treatment, Quality of Life and General Health of Type 2 Diabetes Patients with Inadequate Glycemic Control from North-Eastern Romania

Abstract: Type 2 diabetes mellitus (T2DM) undermines health and quality of life (QoL). This cross-sectional study surveyed 138 consenting T2DM patients from North-Eastern Romania with regard to their satisfaction with treatment, diabetes-related impact on QoL, and general health. The Romanian versions of Diabetes Treatment Satisfaction Questionnaire (DTSQ), Audit of Diabetes Dependent Quality of Life (ADDQoL-19), and 36-Item Short Form Health Survey (SF-36) questionnaires were used. Self-reports were analyzed in conjunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 60 publications
0
10
0
5
Order By: Relevance
“…Ser idoso também afetou mais a qualidade de vida em 5 estudos. 4,9,10,15,16 Usar insulina promoveu qualidade de vida inferior em 4 artigos. 4,9,13,15 .…”
Section: Métodounclassified
See 2 more Smart Citations
“…Ser idoso também afetou mais a qualidade de vida em 5 estudos. 4,9,10,15,16 Usar insulina promoveu qualidade de vida inferior em 4 artigos. 4,9,13,15 .…”
Section: Métodounclassified
“…4,9,10,15,16 Usar insulina promoveu qualidade de vida inferior em 4 artigos. 4,9,13,15 . A obesidade afetou negativamente a qualidade de vida em 2 estudos.…”
Section: Métodounclassified
See 1 more Smart Citation
“…In clinical trials and in practice, bicarbonate administration in DKA has not been shown to be useful in the clinical and biochemical recovery of patients and it is even associated with delayed disappearance of ketone bodies and lactate levels. In addition, bicarbonate can depress cardiac activity, and increase intravascular volume at risk of pulmonary edema as it is hypertonic and hyperosmolar (12)(13)(14)(15)(16).…”
Section: Potassium Level (K)mentioning
confidence: 99%
“…It is manifested especially in the tissues that depend on the action of insulin for intracellular transport of glucose: liver, muscle and adipose tissue. The effects of IR are, however, multiple, as insulin exerts physiological actions on carbohydrate, lipid and protein metabolism, as well as on endothelial function ( 2 ).…”
Section: Introductionmentioning
confidence: 99%